DETECTION OF MYCOPLASMA DISPAR IN BOVINE RESPIRATORY DISEASE BY POLYMERASE CHAIN REACTION ASSAY IN SULAIMANIYAH CITY - Shilan Faqe Muhammad Salih, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to identification and detection of Mycoplasma dispar by conventional real-time polymerase chain reaction (PCR) assays followed by routine hematoxylin & eosin technique to further confirmation of Mycoplasma species related to the lesions observed in diseased calves. Ten samples of infected lung tissue were gathered and fixed in 10% neutral buffered formalin and handled for making a microscopic slide after confirming Mycoplasma dispar infection by PCR. Histopathological examination of the lung revealed two types of pneumonia; chronic suppurative pneumonia in 60% of the cases and 40% of diffuse interstitial pneumonia. Mycoplasma dispar was confirmed based on genetic analysis. Slemani/2018 field isolate showed 99.84% homologies with four reference isolates of Mycoplasma dispar in NCBI GenBank. Phylogenetic analysis indicated a close relation to Mycoplasma ovipneumoniae, Mycoplasma hyopneumoniae, and Mycoplasma flocculare, often isolated from sheep and goats. Therefore, further study is crucial to identify Iraqi livestock's circulating Mycoplasma species related to respiratory diseases.